DEVELOPMENT OF DIGITAL-BASED CREATIVE ECONOMY LEARNING AND LOCAL WISDOM TO CULTIVATE 4C SKILLS IN SOCIAL STUDIES LEARNING - Nur, Muhammad; Hardianti, Retno Ayu; Rismawati, Kharina; Cempaka, Soekma; Wakhid, Sulthon Esa Nur (Universitas Negeri Makassar, 2025)
This study aims to develop a digital-based creative economy learning model and local wisdom to foster 4C (Critical Thinking, Communication, Collaboration, and Creativity) skills in social studies learning at the secondary school level. The research methods used include needs analysis, identification of obstacles and opportunities, and design of learning models. Needs analysis is conducted through interviews and surveys involving teachers and students. The results show an urgent need to utilize digital technology in social studies learning and integrate local wisdom. Key barriers identified include limited technology infrastructure, lack of teacher competence, and resistance to changes in learning methods. On the other hand, there are significant opportunities such as government policy support for the digitalization of education and high student interest in the use of technology. The designed learning model combines digital technology with local wisdom through the use of learning videos, simulations, digital applications, collaborative projects, and 4C skill assessments. Model trials at SMP Negeri 12 Bandung showed significant improvements in student engagement and student 4C skills development. Revision of the model based on feedback from teachers and students resulted in increased interactivity of the material and effectiveness of collaborative tasks. The widespread implementation of this learning model shows positive results, with improved critical thinking, communication, collaboration, and creativity skills of students. Teachers report increased student motivation and enthusiasm in learning. The conclusion of this study is that digital-based creative economy learning models and local wisdom are effective in improving students' 4C skills. Research recommendations include improved technology infrastructure, ongoing training for teachers, development of relevant learning materials, and stronger policy support. This research is expected to contribute significantly to innovation in social studies learning and the development of students' skills to face challenges in the digital era.